2014
DOI: 10.1002/jhm.2154
|View full text |Cite
|
Sign up to set email alerts
|

Discharge before noon: An achievable hospital goal

Abstract: BACKGROUND Late afternoon hospital discharges are thought to contribute to admission bottlenecks, overcrowding, and increased length of stay (LOS). In January 2012, the discharge before noon (DBN) percentage on 2 medical units was 7%, below the organizational goal of 30%. OBJECTIVE To sustainably achieve a DBN rate of 30% and to evaluate the effect of this intervention on observed‐to‐expected (O/E) LOS and 30‐day readmission rate. DESIGN Pre‐/post‐intervention retrospective analysis. SETTING Two acute care inp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
131
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(137 citation statements)
references
References 7 publications
(15 reference statements)
4
131
2
Order By: Relevance
“…Family meetings and disposition planning occur throughout a patient's stay in the hospital. There is an effort at Stanford Hospital to discharge patients by noon based on evidence that early discharges help reduce patient capacity bottlenecks 14. Each member of the care team has a specific role in the discharge process that is described in table 2.…”
Section: Methodsmentioning
confidence: 99%
“…Family meetings and disposition planning occur throughout a patient's stay in the hospital. There is an effort at Stanford Hospital to discharge patients by noon based on evidence that early discharges help reduce patient capacity bottlenecks 14. Each member of the care team has a specific role in the discharge process that is described in table 2.…”
Section: Methodsmentioning
confidence: 99%
“…5 Previous reports have revealed that staff-led interventions can improve discharge times, and that timely discharge decreases emergency room and surgical boarding. 31, 38 While 78 minutes in isolation may not seem to be a meaningful improvement in discharge time, on a system level such modest, incremental gains have a substantial impact on patient flow through precious hospital resources. 5 …”
Section: Discussionmentioning
confidence: 99%
“…This initiative focused on newer metrics of throughput, such as specific time of discharge and discharge by noon. 7, 31, 32 Here we discuss how the vascular surgery division at our academic medical center utilized a systematic approach to identify barriers to efficient patient throughput and successfully implemented a patient flow intervention.…”
Section: Introductionmentioning
confidence: 99%
“…There was a trend toward an earlier median time of discharge, comparable to other EIDD interventions. 4,10 This increase in EIDD proportion occurred in the setting better coordination of discharge day activities, specifically early-in-day administration of the final methylprednisolone dose. Preparation for this early dose administration was made at time of admission through order entry using the developed intervention order set.…”
Section: Discussionmentioning
confidence: 99%